Cardiorespitory Exercise Model Based Waste Utilization for Elementary School Students - Bayu Prasetio; Arisman (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
The goal to be achieved from this development research is to produce products in the form of waste utilization model books for elementary school students so as to provide guidance for physical education teachers in providing fun, creative and meaningful learning. This study used research and develompent (RnD) method from barg and gall consisting of ten steps, the subjects used in this study were students of SDN Tanjungsari and SDN Blanakan with a total of 68 subjects. The design of the experiment research is one group pretest posttest design. The stages of this study are: introduction research, expert test, large group test small group test and effectiveness test. The effectiveness test in this study used the Harvard Step Test. The results of the model effectiveness test are known that the waste utilization model for physical fitness there is an increase, the pretest obtained an average figure of 33.57 and posttest obtained an average figure of 36.63. From the data can be concluded there is an increase after treatment. The results of the effectiveness test showed the results of t-count = 7818, df = 62 and p-value = 0.00 < 0.05, meaning that the physical fitness exercise model for elementary school students before and after treatment there was a significant difference. It can be concluded that the waste utilization model for physical fitness of elementary school students, effective and able to improve physical fitness